Penerapan Sanksi Terhadap Tindak Pidana Penghinaan Dalam Undang-Undang Informasi Dan Transaksi Elektronik - Sry Wahyuni; Helfira Citra; Elwidarifa Marwenni (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
The main problem of this research is the Application of Sanctions Against Criminal Acts of Humiliation in the Information and Electronic Transaction Law. This problem is divided into two sub-discussions, namely, first, how is the application of sanctions against criminal acts of humiliation in the Information and Electronic Transaction Law, second, what is the form of sanctions imposed on perpetrators of criminal acts of humiliation according to the ITE Law. normative juridical problems, namely conceptualizing law as norms, rules, principles, using a statutory approach that is described descriptively based on problems with various legal rules and literature, as well as seeking a legal opinion on the problem that is the object of the problem.